Teaching, learning and teacher education - Moreno Herrera, Lázaro [Herausgeber]; Teräs, Marianne [Herausgeber]; Gougoulakis, Petros [Herausgeber] (Premiss, 2020)
This book is an outcome of the international conferences organised yearly since 2012 by the research group VETYL (Vocational Education & Training/Yrkeskunnande och Lärande), at the Department of Education, Stockholm University, Sweden. The texts in this volume are selected papers submitted to the VIII Stockholm International Conference of Research in VET initially planned for May 2020. As a consequence of the Covid 19 pandemic the conference was postponed for 2022. "The title of this volume 'Teaching, Learning and Teacher Education' serves as an umbrella where comparative analysis as well as other research outcomes of cross-national interest are presented. Teaching and learning in VET is characterized by a diversity of teaching contexts which poses considerable challenges to organization of the learning process and the learning process itself. Several of the contributions present research outcomes related to various aspects of teacher education, such as: motivation for the teaching profession, Why Do Professionals Want to Become Teachers?" (Text exctract, BIBB-Doku)
Keywords: L Lehren & Lernen; P 3.2.3 Lehrer; P 3.2.2 Weiterbildner; Lernen; Lernmethode; Unterricht; Unterrichtsmethode; Berufsschullehrer; Lehrerbildung; Weiterbildner; Qualifizierung